Tanggung Jawab Notaris Dalam Pelanggaran Kode Etik Notaris - Saly, Jeane neltje; Retaly, Andrea Tamaranova; Shindy, Felicia; Wathan, Bilqis Alifia; Nathanael, Daven; Widjaja, Jason Marcellino (Jurnal Ilmiah Wahana Pendidikan, 2023)
The Code of Ethics is crucial in the Notary profession. The Code of Ethics functions as a moral principle and reference for Notaries to carry out their interests. The Notary Code of Ethics exists in various sources. From these sources it can be seen the obligations and also things that are prohibited. Notaries are required to follow the existing Code of Ethics and if a violation occurs, certain steps can be followed up to impose sanctions as a form of notary accountability. The research uses normative methods with primary materials, namely laws and secondary materials, namely legal journals and information from the internet. Research is expected to be a means of education and affirmation regarding the Notary Code of Ethics itself.